2021
DOI: 10.1002/cssc.202100255
|View full text |Cite
|
Sign up to set email alerts
|

Application of 2D Materials to Potassium‐Ion Hybrid Capacitors

Abstract: Metal‐ion hybrid supercapacitors (MICs) are a new type of electrochemical energy storage (EES) device, consisting of a battery‐type electrode and a supercapacitor (SC)‐type electrode. Exhibiting the advantages of both batteries and SCs (e. g., good energy density, excellent power density and long cycle life), these advanced energy storage devices have considerable commercial application prospects. Among MICs, potassium‐ion hybrid supercapacitors (PICs) have several further advantages, including abundancy of re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 31 publications
(18 citation statements)
references
References 68 publications
(104 reference statements)
0
17
0
Order By: Relevance
“…Numerous different MICs have been reported in the literature including the lithium-ion (LIC), sodium-ion (NIC), potassium-ion (KIC) and zinc-ion capacitors (ZIC), among others. [116][117][118][119] Comte et al reported the first hybrid KIC using graphite (battery type) as the anode, activated carbon (capacitor type) as the cathode and a 0.8 m KPF 6 EC:DMC electrolyte. [120] During the charging process, the K + ions are intercalated into the anode while the PF 6 − anions in the electrolyte are adsorbed on the cathode surface, forming an electric double layer.…”
Section: Hybrid Potassium-ion Capacitor (Kic)mentioning
confidence: 99%
“…Numerous different MICs have been reported in the literature including the lithium-ion (LIC), sodium-ion (NIC), potassium-ion (KIC) and zinc-ion capacitors (ZIC), among others. [116][117][118][119] Comte et al reported the first hybrid KIC using graphite (battery type) as the anode, activated carbon (capacitor type) as the cathode and a 0.8 m KPF 6 EC:DMC electrolyte. [120] During the charging process, the K + ions are intercalated into the anode while the PF 6 − anions in the electrolyte are adsorbed on the cathode surface, forming an electric double layer.…”
Section: Hybrid Potassium-ion Capacitor (Kic)mentioning
confidence: 99%
“…Li-ion capacitors (LICs) are made up of a capacitor-type cathode, one battery-type anode, and one appropriate electrolyte [ 15 , 69 , 70 , 71 , 72 , 73 , 74 ]. They rely on the surface reaction of the cathode and the lithiation/electrolysis of the anode to achieve energy storage and conversion [ 14 , 16 , 17 , 18 ]. Owning to the higher power density together with the longer cycle life than those of Li-ion batteries, as well as higher energy density than that of supercapacitors, LICs are regarded to be one of the most prospective electrochemical energy storage devices.…”
Section: Application Eg-based Materials In Supercapacitormentioning
confidence: 99%
“…When compared to rechargeable batteries, supercapacitors exhibit quicker charging and discharging (supercapacitors: 1–10 s vs. battery: 0.5–5 h), higher power density (supercapacitors: 500–10,000 W kg −1 vs. battery < 1000 W kg −1 ), remarkable longer life (supercapacitors > 500,000 h vs. battery: 500–1000 h), together with safer operation [ 2 , 11 , 12 , 13 ]. However, the low energy density of supercapacitors (supercapacitors: 1–10 W h kg −1 vs. battery: 10–100 W h kg −1 ) is a major challenge to the further development of supercapacitors [ 2 , 11 , 14 , 15 , 16 , 17 , 18 ]. To overcome this, most studies have focused on developing high-performance supercapacitor electrode materials.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nowadays, many types of anode materials, such as carbonaceous materials, [ 4 ] transition‐metal oxides/sulfides, [ 5 ] 2D materials, [ 6 ] metal chalcogenides‐based materials [ 7 ] and organic materials [ 8 ] have been developed for potassium‐ion batteries (KIBs) or KICs. Especially, nanostructured carbon materials such as carbon nanotube, [ 9 ] graphite materials, [ 10 ] porous carbon, [ 11 ] and hollow carbon nanospheres [ 12 ] have been extensively studied as promising anodes for KIBs or KICs owing to their safety, low toxicity, and chemical stability.…”
Section: Introductionmentioning
confidence: 99%